The earthquake effect of multi-storey building due to surrounding earthquake in Malaysia - Nuraziemah, Zainal (2016)
Most structures in Malaysia were designed without considering for seismic factor during its service lifetime. However, in recent years Malaysia has experienced the effects of earthquake such as at Ranau, Sabah and was impacted from Tsunami on 2004. Besides that, earthquake originated mainly from epicenters in the western zones arising from the Sumatra and Philippines. The aim of this study is to study the behaviour reinforced concrete of Multi-storey building that subjected to earthquake excitation. Thus, this research present comparative analysis using SAP2000 and Esteem 8 software (shear forces and moment resistances). During this phase, all the information, data, studies and facts that are related to study, should be known. The information to be collected is useful for model and analyze our structure. The information and data that required are architectural drawing of the building and the earthquake data. Raw data of earthquake originated from Tsunami in Aceh which recorded in Malaysia seismic stations will be collected from Malaysian Meteorological Department (MMD). Based on architecture drawing of multi-storey building, the structural drawing should be design using Esteem 8 and SAP2000 software as a planned. There the multi-storey reinforced concrete building which were design 5th floor level of building. The designed for both software were considering earthquake factor and data. The best result will be compare to select the best software for considering earthquake design for multi-storey building. Other than that, this study are to determine the best mode shape of free vibration analysis. There have 12 mode shape with different natural period and frequencies. Results such as the natural frequencies, vibration modes of the structure, bending moment and shear force etc. are collected and analyzed. Generally, the multi-storey structure with consideration of seismic ground motion is still within members capacity desirable range.